Values, regulation, and species delimitation - Conix, Stijn (Zootaxa, 2018)
Garnett and Christidis (2017) [hereafter GC] recently proposed that the International Union of the Biological Sciences should centrally regulate the taxonomy of complex organisms. Their proposal was met with much criticism (e.g. Hołyński 2017; Thomson et al., 2018), and perhaps most extensively from Raposo et al. (2017) in this journal. The main target of this criticism was GC’s call to, first, “restrict the freedom of taxonomic action”, and, second, to let social, political and conservation values weigh in on species classification. Some commentators even went as far as to draw a comparison with the infamous Lysenko-case of state-controlled and heavily restricted science (Raposo et al. 2017, 181; Hołyński 2017, 12). This comment will argue, without thereby endorsing GC’s position, that these two aspects of their views need not be as threatening as this comparison suggests, and indeed are very reasonable.